Social Subjets, Schools and Rural Communities. Disputes of Power in the Scenario of the Buenos Aires Campaign (1810-1875) - Lionetti, Lucía (Historia y Memoria de la Educación, 2018)
What kind of schools existed in a rural world marked as an uncivilised society with political instability and fluid inter and intra-ethnic contact? For what purposes was this schooling planned and what role did it play in shaping the political order? What relationships were interwoven between civil authorities, religions, inhabitants and preceptors? These questions are the starting point for an examination of the presence of elementary schools in Buenos Aires (Buenos Aires province) and of the initiative taken to extend the civilizing process of literacy; in a country seen as underdeveloped, this represented a sponsorship of «rural politics». Conflicts, difficulties, types of educational practices and the profile of preceptors will all be explored from a select bibliography in conjunction with the consulted document repositories - local files, press and official documents. This rural schooling, before the establishment of the common free education system in 1875, revealed tensions but also agreements between society, its «common customs» and the political power which sought to become consolidated in the province